(untitled) - Andreosso-O'Callaghan, Bernadette (New York, 2001)
Offering a critical reappraisal of the causes of the 1997 Asian crisis and of its impact on the strategies of firms, this book is essential reading for anyone who wants to understand how firms have responded to the changes brought about by the crisis, and what the major structural developments have been in the Asian economies since the late 1990s. Through the use of up-to-date statistical data and theoretical tools the contributors convey the excitement that pervades recent developments in Asia.
Keywords: Strategic planning,Industrial management,Corporations,Investments, foreign,Financial crises; Asia,Asia,Asia,Asia,Asia